T-2 toxin triggers lipid metabolism disorder and oxidative stress in liver of ducks - Keying An; Bozhi Shi; Xueze Lv; Yanhan Liu; Zhaofei Xia (Ecotoxicology and Environmental Safety)
T-2 toxin (T-2) is a highly toxic mycotoxin that threatens organism health, yet its hepatoxicity on ducks remains unknown. The present study aimed to assess the hepatoxicity and redox reactions induced by T-2 in ducks. Sixty 7-day-old ducklings were divided into 4 groups and exposed to 0, 200, 400 and 800 μg/kg bodyweight of T-2 through oral gavage for 2 weeks. The growth performance, liver histopathology, biochemical indicators, antioxidant capacity and hepatic damage-related genes of ducks were analyzed. The results revealed that 800 µg/kg T-2 inhibited the growth and feed intake of ducks, whereas liver index increased with the elevation of T-2 concentration. Histological examinations exhibited that T-2 caused hepatic cord disappeared and severe steatosis. Moreover, serum AST, ALT and TG were substantially higher in 400 μg/kg group, while γ-GT and ALB were reduced under 800 μg/kg T-2 exposure. In addition, significant increase of malondialdehyde (MDA) in liver, decrease of hepatic total antioxidant capacity (T-AOC) and serum glutathione peroxidase (GPx) were observed in all T-2 groups. Furthermore, T-2 disrupted lipid metabolism and oxidative stress-related genes expression in liver. The transcript level of fatty acid binding protein 1 (FABP1) was markedly raised in all T-2 groups, and hepatic acyl-CoA oxidase 1 (ACOX1) was significantly raised in 200 and 400 μg/kg T-2 groups. Under 800 μg/kg T-2, significant induction of hypoxia inducible factor-1 alpha (HIF-1α), and downregulated peroxisome proliferator-activated receptor (PPAR)-alpha, carnitine palmitoyl transferase 1A (CPT1A), peroxisome proliferator-activated receptor gamma coactivator 1alpha (PGC-1α), GPx1, catalase (CAT) mRNA levels were observed. Therefore, we conclude that T-2 caused liver injury through lipid metabolism disruption and oxidative stress in ducks, which reinforces understanding about the hepatoxicity mechanisms of T-2 and provides new targets for detoxication and prevention.